The Influence of Green Innovation, Sustainability Reports, and Going Concern Opinion on Company Value - Anggraini, Sylvia Putri; Arieftiara, Dianwicaksih (EQUITY, 2023)
This study aims to determine the effect of green innovation, sustainability reports, and going concern opinion on firm value with firm size as the control variable. This study uses a quantitative method with secondary data types with a sample of manufacturing and mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2020. Based on the purposive sampling technique with unbalanced panel data, 101 samples were obtained in this study. The data analysis technique used is Multiple Linear Regression analysis using STATA version 14 with a significance level of 5%. Meanwhile, going concern opinion has a significant negative effect on company value. It is hoped that this research can contribute to capturing the level of green innovation and its impact on company value, by also considering the quality of sustainability reports and going concern opinions. Keywords: Firm Value, Going Concern Opinion, Sustainability Report, Green Innovation.